Analisis fungsi keuntungan usahatani kacang hijau (Phaseolus ra-diatus L.) di Kabupaten Malaka Provinsi Nusa Tenggara Timur - Maria Virgilia Balok Klau; Ida Nurwiana Nurwiana; Marthen R. Pellokila (Holistic: Journal of Tropical Agriculture Sciences, 2023)
The cause of the low productivity of mung beans is partly due to the inefficient use of production factors, which will theoretically affect the profit level of farming. This study specifically aims to analyze the allocation of the use of production inputs and to analyze the profit function of mung bean farming. Data collection used a survey method by interviewing 52 farmers in Central Malaka District, Malaka District, East Nusa Tenggara. Data analysis used a quantitative descriptive method, through the analysis of farm costs, and analysis of the Cobb-Douglass Unit Output Price profit function. The results showed that mung bean farming was profitable with a profit rate of around 7.66 million rupiah per hectare. The allocation of farming inputs that significantly affect production are land area, seeds, and pesticides, with coefficient values ​​of 0.96, 0.56 and -0.49, respectively. Meanwhile, variable inputs that significantly affect profits are fertilizer prices, pesticide prices, and labor costs, with coefficient values ​​of -0.43, 0.43, and -0.75, respectively. These results inform several aspects: (a) increasing the area of ​​land and seeds increases production, conversely increasing the use of pesticides can reduce production and therefore it is necessary to adjust the correct dosage, (b) the use of fertilizers is not significant to production caused by the application dose is too low, ( c) the use of labor is not significant to production and its addition reduces profits, so it needs to be more efficient in its use by prioritizing the quality of the workforce.